2013
DOI: 10.1007/s11274-013-1287-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential of European wild strains of Agaricus subrufescens for productivity and quality on wheat straw based compost

Abstract: The Brazilian almond mushroom is currently cultivated for its medicinal properties but cultivars are suspected all to have a common origin. The objective of this work was to assess the potential of wild isolates of Agaricus subrufescens Peck (Agaricus blazei, Agaricus brasiliensis) as a source of new traits to improve the mushroom yield and quality for developing new cultures under European growing conditions. The wild European strains analysed showed a good ability to be commercially cultivated on wheat straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Some studies reported the influence of the N content and the C/N ratio in the production of the compost for A. subrufescens production Llarena-Hernández et al, 2014;PardoGiménez et al, 2014). In Brazil, the compost used for A. subrufescens production has a C/N ratio close to 27/1 (at the end of Phase II), and in Europe, the compost has a C/N ratio close to 18/1 (at the end of Phase II) (Andrade et al, 2007;Siqueira et al, 2011;Zied et al, 2011b;Llarena-Hernández et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported the influence of the N content and the C/N ratio in the production of the compost for A. subrufescens production Llarena-Hernández et al, 2014;PardoGiménez et al, 2014). In Brazil, the compost used for A. subrufescens production has a C/N ratio close to 27/1 (at the end of Phase II), and in Europe, the compost has a C/N ratio close to 18/1 (at the end of Phase II) (Andrade et al, 2007;Siqueira et al, 2011;Zied et al, 2011b;Llarena-Hernández et al, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different steps of production, compost (formulation, phase I and II) is thought to be one of the most important, because it directly influences the productivity and quality of the mushrooms (Horm and Ohga, 2008;Matute et al, 2010;Llarena-Hernández et al, 2013;Wang J. T. et al, 2013;Souza et al, 2014). To improve the compost process, substrate supplementation has been used to provide nutrients to the developing mushroom, reducing the cultivation cycle and increasing productivity by up to 30% .…”
Section: Introductionmentioning
confidence: 99%
“…Even though A. subrufescens and Agaricus bisporus, the button mushroom, belong to the distinctly different Agaricus sections Arvenses and Bivelares, respectively, both are secondary decomposers and can be cultivated on similar substrates (Largeteau et al 2011;Llarena-Hernández et al 2013). A. subrufescens is, to our knowledge, the Agaricus species having the broadest climatic and geographical range (Peterson et al 2000;Kerrigan 2005;Wisitrassameewong et al 2012a, b;Parra 2013;Gui et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…subrufescens grows at higher optimal temperatures than A. bisporus: for instance in previous studies [19], the authors found that optimal temperatures for mycelial growth was around 30 8C, depending on the strains studied. De Mendoca et al [16] reported optimal temperatures ranging from 25 to 28 8C and Llarena et al [20] optimal temperatures varying from 26 to 30 8C, with a similar range of variation for cultivars and wild strains. Long-time storage at low temperatures such as 4 8C is known to be lethal for A. subrufescens [21].…”
Section: Tablementioning
confidence: 99%